STUDI DESKRIPTIF KUALITATIF STRATEGI PENYIARAN RADIO LPP RRI SURAKARTA - Fitriani, Afika Nur; Maserona, Lukas (Solidaritas, 2025)
This study aims to analyze the communication strategy implemented by RRI Pro 2 Surakarta in the context of broadcasting in the digital era. Using a qualitative descriptive method, this study identifies the steps of the communication strategy which include determining the audience, setting goals, formulating messages, selecting methods, and selecting media. In addition, this study also reveals the communication techniques used, such as canalizing, informative, and persuasive. The results of the study indicate that RRI Pro 2 Surakarta faces several obstacles in the process of delivering information and physical obstacles that affect the effectiveness of communication. Keywords: RRI Pro 2 Surakarta, communication strategy, broadcasting, digital media.